Analisis Keterbatasan Regulasi Sanksi Malpraktik Tenaga Medis Asing dan Konsekuensinya Terhadap Penegakan Hukum di Indonesia - Indrawan Guamo (Jurnal Hukum Caraka Justitia, 2025)
Indonesia as a developing country, upholds human rights, including the right to health guaranteed in the 1945 Constitution. In this context, the presence of foreign medical personnel is an important part in supporting national health services. However, regulations governing foreign medical personnel, especially regarding malpractice sanctions and supervision mechanisms, still have significant weaknesses that have an impact on patient protection and the effectiveness of law enforcement. This study aims to identify the weaknesses of these regulations and analyze the consequences of their limitations on the legal system in Indonesia. The method used is normative legal research with a normative juridical approach, examining laws and regulations, legal literature, court decisions, and legal doctrine qualitatively. The results reveal that the existing administrative and criminal sanctions are still not firm and specific enough for foreign medical personnel, while supervision and competency verification have not been effective and integrated. In addition, complaint mechanisms and legal protection for patients who are victims of malpractice are still difficult to access, and there are ambiguities in legal jurisdiction, especially in cross-border cases.